A Critical Look into the Language Ideologies of Filipino ESL Teachers in Korean-run ESL Centers in the Philippines - de Guia, Rowell (Journal of Language and Literature Studies, 2025)
This study delves into the language ideologies of Filipino teachers of English as a second language (ESL) who work at an ESL center for Korean students in the Philippines. Using a critical discourse analysis (CDA) framework, the research examines the teachers’ written accounts of their work experiences to uncover their core beliefs about English language proficiency. A key goal of the study is to identify the political and economic interests that shape their ideologies. The data analysis was structured around CDA's three-dimensional approach: description, interpretation, and explanation. The description phase focused on the linguistic features of the teachers’ written accounts, identifying the specific language choices that pointed to their underlying ideologies. The interpretation phase critically examined the broader social, political, and economic contexts of the teachers’ workplace to understand how these realities influenced their experiences and shaped their beliefs. Finally, the explanation phase explored how these ideologies reflect and reinforce existing practices and power dynamics within the field of ESL teaching. The findings of this study revealed three dominant language ideologies held by the teachers: grammar supremacy, non-native linguistic flexibility and autonomy, and language as economic and social capital. These ideologies are not isolated but are a direct result of the political forces present in Korean society, as well as the socio-economic conditions both within and outside the Philippines, and significantly influence the ESL teachers’ instructional orientation, self-valuation, their valuation of English language skills, and social positioning. Thus, the study recommends academic institutions and ESL centers around the world to actively counter inequalities in ESL teaching by formally recognizing and valuing the linguistic and cultural capital that non-native English-speaking teachers bring to the classroom.